Electrodeposition of Cu2S nanoparticles on fluorine-doped tin oxide for efficient counter electrode of quantum-dot-sensitized solar cells - Wang, Jia; Rahman, Md. Mahbubur; Ge, Chuangye; Lee, Jae-Joon (Journal of industrial and engineering chemistry (Seoul, Korea), 2018)
[Display omitted] •Cu2S was electrodeposited onto FTO by a single-step potentiostatic method.•The Cu2S–CE showed excellent catalytic activity for the reduction of Sn2−.•This Cu2S–CE based QDSSC outperformed the PV performance of a Pt–CE based QDSSC.•A maximum PCE of 4.24% was attained in a CdS/PbS/ZnS QD-sensitized cell. This study demonstrated a single-step potentiostatic method for the electrodeposition of copper (I) sulfide (Cu2S) nanoparticles onto fluorine-doped tin oxide (FTO) electrode from an aqueous solution of CuCl2 and thiourea (TU) to develop counter electrodes (CEs) for quantum-dot sensitized solar cells (QDSSCs). The homogeneously distributed and optimized Cu2S–CE exhibited an improved catalytic activity in the reduction of polysulfide (S2−/Sn2−) electrolyte, which resulted in a power conversion efficiency (PCE) of 4.24% with a short-circuit current density (Jsc), open-circuit voltage (Voc), and fill factor (FF) of 19.60mA/cm2, 0.445V, and 48.62%, respectively, for PbS/CdS/ZnS QDs sensitized QDSSCs, while the Pt counterpart exhibited a PCE of 1.17%. The superior photovoltaic performance of this Cu2S–CEs based QDSSC compared to the Pt counterpart is due to its greater electrocatalytic activity and lower charge transfer resistance (RCT) at the Cu2S–CEs/(S2−/Sn2−) interface. This strategy provides an effective, low-cost, and non-Pt electrode for QDSSCs, which is promising for other electrochemical applications.